2017
DOI: 10.1111/sode.12272
|View full text |Cite
|
Sign up to set email alerts
|

Cultural socialization of toddlers in emotionally charged situations

Abstract: This study examined mothers' responses to foster emotional competence from a cultural perspective. Fifty-one European American, 52 Turkish, and 40 Romanian mothers of 2-year-old children provided open-ended responses to vignettes of anger-, sadness-, fear-, and happiness-eliciting situations. Mothers' responses were compared between the family models of independence (United States) and psychological interdependence (Turkey, Romania) to understand cultural variations. To anger, all mothers endorsed problem-focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…In terms of emotion regulation, Romanian mothers of preschoolers emphasize teaching their children to down regulate anger and sadness, while in the case of happiness, they tend to match their children’s expressions (Denham et al, 2004). More recently, Corapci et al (2017) also found evidence for the emotional interdependence model in Romanian mothers, when assessing interview responses targeting toddler socialization in emotionally charged situations.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…In terms of emotion regulation, Romanian mothers of preschoolers emphasize teaching their children to down regulate anger and sadness, while in the case of happiness, they tend to match their children’s expressions (Denham et al, 2004). More recently, Corapci et al (2017) also found evidence for the emotional interdependence model in Romanian mothers, when assessing interview responses targeting toddler socialization in emotionally charged situations.…”
Section: Introductionmentioning
confidence: 90%
“…Like other collectivist societies undergoing significant sociodemographic changes, Romania is considered representative for the emotional interdependence model, given the major shifts toward democracy, market economy, urbanization, and globalization, over the post-communist period (since 1990), augmented after having joined the European Union in the last decade (Gavreliuc and Ciobotă, 2013; Corapci et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naturalistic home observations also reveal that higher SES Turkish mothers of 3-year-old children are less likely to display controlling (e.g., verbally or physically intruding the child) and non-responsive behaviors than lower SES mothers (Akcinar and Baydar, 2014; Baydar and Akcinar, 2015). A recent study on emotion socialization has revealed that middle-high SES Turkish mothers endorse encouragment of the child for independent coping along with comforting and reasoning responses, suggestive of a combination of autonomy- and relatedness-orientation (Corapci et al, 2018). These results suggest that higher SES Turkish mothers convey messages about the autonomous-related self in socializing children.…”
Section: Cultural Context Of Turkish Familiesmentioning
confidence: 99%